2017
DOI: 10.17712/nsj.2017.1.20160303
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of CYP2C19 genetic polymorphism on clopidogrel response in patients with ischemic stroke from Saudi Arabia

Abstract: Objective:To elucidate the degree of genetic polymorphisms CYP2C19 (CYP2C19*2, CYP2C19*3) of key drug metabolizing enzymes on the antiplatelet effect of clopidogrel response in patients with acute ischemic stroke from Saudi Arabia.Methods:A case-control study carried out at Neurology Clinics at Asser Central Hospital, Abha, Kingdom of Saudi Arabia from October 2015 to January 2016 and included 25 stroke patients responding to clopidogrel therapy and 25 stroke patients non responding to clopidogrel monotherapy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Thus, it is recommended that monotherapy with clopidogrel is appropriate if patients are intolerant to aspirin because of allergy or gastrointestinal side effects or to dipyridamole because of headache. However, the clinical response to clopidogrel varies widely in patients with cardiovascular and/or cerebrovascular diseases and it is closely related to the CYP2C19 gene polymorphism 11 13 . For example, some studies show CYP2C19*2 carriers have lower levels of active clopidogrel metabolites, higher on-treatment platelet aggregation, and higher risk for major adverse cardiovascular events as compared to noncarriers 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is recommended that monotherapy with clopidogrel is appropriate if patients are intolerant to aspirin because of allergy or gastrointestinal side effects or to dipyridamole because of headache. However, the clinical response to clopidogrel varies widely in patients with cardiovascular and/or cerebrovascular diseases and it is closely related to the CYP2C19 gene polymorphism 11 13 . For example, some studies show CYP2C19*2 carriers have lower levels of active clopidogrel metabolites, higher on-treatment platelet aggregation, and higher risk for major adverse cardiovascular events as compared to noncarriers 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the influence of CYP2C19 genotypes and metabolizer status on the efficacy of clopidogrel 11 13 . Although these studies consistently suggest CYP2C19 genotypes are closely related to the clopidogrel response, the influence of CYP2C19 metabolizer status on the clopidogrel response is still inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the rs11053646 polymorphism in OLR1 gene was associated, and our results confirm the earlier meta-analysis studies, concluding as may contribute to the risk of disease susceptibility (Au et al, 2015). In Saudi Arabia, there are limited studies have been documented with stroke, and among them, Alhazzani et al (2017) performed the molecular study with CYPC219 genetic polymorphisms and found to be associated. Al-Shenqiti et al (2017) performed the detailed study of stroke who were effected for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Hardy-Weinberg equilibrium was tested and reported in only 9 studies. 28,[30][31][32][36][37][38][39][40]…”
Section: Prevalence Of Explored Genetic Variantsmentioning
confidence: 99%
“…The definition of clopidogrel responsiveness varied across the included studies. Among the 9 studies, the cutoff value for HTPR was expressed using platelet aggregation in 2 studies 26,40 whereas it was expressed as percentage of relative platelet inhibition in 1 study. 31 Two of the studies expressed the cutoff value for HTPR by the PRU.…”
Section: Clopidogrel Response Definitionmentioning
confidence: 99%